Study of Soil Conservation Programme for Agricultural Land - Planning Commission (Planning Commission, 1962)
Together with moisture, soil provides the physical base of agricultural production. Quantity, quality and frequency of economic output from any piece of land are conditioned in a large measures by the nature and characteristics of the soil in its upper layer, a suitable depth of which takes about a hundred years or more for its natural formation. The loss of this valuable top soil results in a deterioration of the quality of land so much so that its use pattern has to undergo a complete change for the poorer. The loss of the top soil is a slow, gradual process which can, however, be accelerated by injudicious or ignorant human action in the form of neglectful or faulty methods of husbandry that tend to interfere with the cyclical process of nature and, in particular, accentuate the destructive part of it.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission